Correction: Study on photoelectric characteristics of monolayer WS2 films. Issue 67 (28th November 2019) - Wang, Lin; Wang, Wenyan; Wang, Quan; Chi, Xiaochun; Kang, Zhihui; Zhou, Qiang; Pan, Lingyun; Zhang, Hanzhuang; Wang, Yinghui
Abstract : Correction for 'Study on photoelectric characteristics of monolayer WS2 films' by Lin Wang et al., RSC Adv., 2019, 9, 37195–37200.